First report of a ‘Candidatus phytoplasma pyri’ strain in Argentina - Fernandez, Franco Daniel; Marini, Diana Beatriz; Farrando, Roberto Jes; Conci, Luis Rogelio (Springer, 2018)
During the 2015 growing season, peach plants (Prunus persica) showing chlorotic, curling leaves and midrib thickening were detected in production fields in Mendoza province (Midwest region, Argentina). These symptoms resemble those described for Peach Yellow Leaf Roll disease, a ‘Candidatus Phytoplasma pyri’ related strain. By PCR of the 16S rDNA gene, a phytoplasma was detected in symptomatic samples. The RFLP profile, sequence identity and phylogenetic analyses showed that the Peach Yellows phytoplasma belongs to group 16SrX-C and is identical to those described as ‘Candidatus Phytoplasma pyri’. This is the first report of a phytoplasma from 16Sr group X infecting peach trees in Argentina and in South America.